Enhancing Repurchase Intention in Retail: the Role of Customer Satisfaction, Service Quality, and Product Assortment - Tessa Desara; Verinita Verinita; Maruf Maruf; Tedi Hidayat (Enrichment : Journal of Management, 2021)
High competition in retail sector has encourage the actors to keep their attention to estimate next sales volume through determine repurchase intention. This study aims to find out the effects of product assortment and service quality on repurchase intention directly, and through mediating impact of customer satisfaction indirectly. We received 222 feedback online questionnaires through the technique of purposive sampling. Then, we were analyzed by assisting of PLS and SPSS Vs. 26 to descriptive analysis and SEM. We found all of the hypothesis proposed are supported, and partial contribution by customer satisfaction in both indirect effects